Removal of the Micropollutants Propranolol Hydrochloride and 2-Naphthol From Water by Pyridine-Functionalized Polymers - Zheng, Qixuan; Unruh, Daniel K.; Hutchins, Kristin M. (Frontiers in Chemistry, 2022)
The number and concentration of micropollutants in aqueous environments are increasing. Two such micropollutants include the pharmaceutical, propranolol hydrochloride, and dye intermediate, 2-naphthol. Here, we describe the synthesis of both linear and crosslinked pyridine-functionalized copolymers that bind and remove propranolol hydrochloride and 2-naphthol from water solutions. Propranolol hydrochloride and 2-naphthol both contain hydrogen-bond-donor groups, and the pyridine moiety on the polymer acts as a hydrogen-bond acceptor to facilitate removal. Copolymers with different amounts of pyridine comonomer are synthesized, and as the amount of the pyridine comonomer is increased, the ability of the polymer to bind and remove the contaminant also increases. The concentrations of propranolol hydrochloride and 2-naphthol decreased by approximately 20-40% and 60-88%, respectively, depending on the polymer type that is used in the binding experiment. A control polymer was synthesized by using styrene in place of the pyridine monomer. In analogous binding experiments, the styrene polymer decreases the concentration of propranolol hydrochloride by 2% and 2-naphthol by 26%. Thus, the binding effectiveness is significantly reduced when the hydrogen-bond-acceptor group is not present on the polymer. We also show that the best performing crosslinked pyridine-functionalized polymer is reusable. Overall, these polymer adsorbents demonstrate the potential of the removal of micropollutants from water.